Advances in Ultra-Coarse-Grained Models for Large Biomolecules (Communications in Computational Chemistry, 2026)
Recent advances in Ultra-Coarse-Graining (UCG) modeling for biological systems have improved both construction strategies and forcefield development. Empirical forcefields remain the primary choice for large systems due to their efficiency and ability to capture conformational dynamics, while non-restraining potentials and multiscale approaches have enhanced predictive capability for complex intermolecular interactions. Although bottom-up methods are currently limited by high parameterization costs, increasing physical interpretability and the growth of biomolecular trajectory databases are expected to make them more feasible and transferable in the future.
Keywords: Ultra-coarse-grained models; proteins; bottom-up; coarse-graining; empirical coarse-grained models